2009
DOI: 10.4088/pcc.08.m00711
|View full text |Cite
|
Sign up to set email alerts
|

Primary Care Evaluation of Mental Disorders (PRIME-MD) Screening for Minor Depressive Disorder in Primary Care

Abstract: Objective: Individuals visiting a primary care practice were screened to determine the prevalence of depressive disorders. The DSM-IV-TR research criteria for minor depressive disorder were used to standardize a definition for subthreshold symptoms.Method: Outpatients waiting to see their physicians at 3 community family medicine sites were invited to complete a demographic survey and the Primary Care Evaluation of Mental Disorders Patient Questionnaire (PRIME-MD PQ). Those who screened positive for depression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 26 publications
0
25
0
3
Order By: Relevance
“…Although the initial questions in the CEG explore the symptoms experienced in the preceding 2 weeks, the algorithm also includes questions about the longitudinal course of symptoms that can aid reaching diagnoses such as dysthymia. The mood disorders module of CEG used in the study has been shown to have excellent positive predictive value, with satisfactory specificity and sensitivity in terms of diagnosis .…”
Section: Methodsmentioning
confidence: 99%
“…Although the initial questions in the CEG explore the symptoms experienced in the preceding 2 weeks, the algorithm also includes questions about the longitudinal course of symptoms that can aid reaching diagnoses such as dysthymia. The mood disorders module of CEG used in the study has been shown to have excellent positive predictive value, with satisfactory specificity and sensitivity in terms of diagnosis .…”
Section: Methodsmentioning
confidence: 99%
“…Cut-off points for high levels for EE and DP were scores >27 and >10, respectively, and the cut-off for low levels for PA was scores <33. Since low scores for PA are considered less important in detecting burnout symptoms,13 burnout was defined as a high score on the DP and/or EE subscales (EE score >27 and/or DP score >10, in accordance with Shanafelt et al11 Depression symptomology was identified using the 2-item Primary Care Evaluation of Mental Disorders (PRIME MD), a standardized depression-screening tool 14…”
Section: Methodsmentioning
confidence: 99%
“…the method was created on the basis of diagnostic and Statistical manual of mental disorders iV th edition (dSm-iV) criteria and is recommended to be used as a screening test for preliminary diagnosis of mental disorders. the preliminary diagnosis of a particular disorder de-mands the presence of a specific number and duration of symptoms according to dSm-iV criteria included in the coding system [9,10]. the assessment of somatoform disorders was excluded from the current analysis, since no objective data on medical health status was available.…”
Section: Methodsmentioning
confidence: 99%